Theoretical framework for improving the records management of retirees in public sector - Abu Bakar, Normashidayu; Mohd Zahibi, Muhammad Faris Hami; Marzuki, Nur Fatin Nazifah; Hamidon, Huda; Mohd Affandi, Najatul Afiqah (Faculty of Information Management, 2025)
This project focuses on the development of a Retiree Records Management System specifically designed for the Jabatan Pendidikan Negeri Kelantan Pension Subunit. The current reliance on manual filing methods using Excel software has proven to be inefficient. This approach is not only slow and prone to inaccuracies but also exposes retiree files to risks of loss and manipulation. The primary objective of this project is to create a web-based system that simplifies and secures the search and management of retiree files. By implementing such a system, we aim to ease the workload of the staff responsible for this task, while enhancing both accuracy and security. The proposed system will allow staff to search for retiree files, add new records, and manage file retention by displaying a list of files scheduled for disposal after a predetermined retention period. Additionally, the system will enable staff to update retiree details accurately and efficiently. It is expected that this solution will significantly reduce the time required for file management, improve data accuracy, and minimize the risk of data loss, benefiting both staff and retirees alike.